Foundations and clinical applications of nutrition : a nursing approach - Grodner, Michele; Long, Sara; Walkingshaw, Bonnie C. (Singapore : Mosby / Elsevier, 2009)
Dicusses and analyzes two USDA guidelines - Dietary Guidelines for Americans 2005 and the MyPyramid Food Guidance System. This title features 'MyPyramid' logo boxes that spotlight critical information as it pertains to chapter content in the basic nutrition chapters. It includes virtual case studies and chapter-by-chapter PowerPoint presentations
Includes index
NUR
Keywords: Nutrition